MODELING THE BEHAVIOUR OF CHEMICAL RESISTANT CONCRETE MODIFIED WITH FLY ASH UNDER DIFFERENT PH ENVIRONMENTS - HAYDAR, RAZ RIZGAR; MOHAMMED, AHMED SALIH (Journal of Duhok University, 2020)
Concrete is the main building unit used in infrastructure and buildings, including dams, swages, and sewage pipes. The main problem in the concrete used in the sewerage pipe or the water treatment system is the erosion when concrete becomes subjected to different pHs. This study’s objective is to evaluate and model the effects of various pHs on plain concrete and concrete modified with fly ash. Water to cement ratio and time of curing were taken as independent variables in the experiment. The main dependent variables are the strengths of compression and tensile of the concrete. From the over 900 data collected, the w/c was ranged between 0.3-0.5. The compression strength varied from 0-88.6 MPa and tensile strength ranged from 0.5-5 MPa. Direct correlations between compression strength and w/c, curing time, pH value and fly ash precentage were not found. From the Nonlinear Model ( NLM) parameters, fly ash percentage has a positive effect on the concrete resisting the different pH values. However, FA% content should not exceed 25% because it will cause the cement to lose its bonding qualities. FA might reduce the rate of penetration of the chemicals and make the concrete resist the chemicals to penetrate further into the interior of the concrete.